The impact of wheat stripe rust in the presence of resistance genes Yr9, Yr10, and Yr15 on gluten proteins: Insights from size-exclusion high-performance liquid chromatography analysis - Ridokunda Sivhada; Willem Boshoff; Angeline van Biljon; Maryke Labuschagne (Applied Food Research)
In the race to overcome the severe effects of climate change on crop production, yield and disease resistance are often prioritised while neglecting the nutritional quality. Wheat stripe rust constrains the photosynthetic functioning of plant leaves, which affects the supply and movement of assimilation products. Bread wheat quality is influenced by genetic and environmental effects and their interactions. The end-use quality of wheat is largely determined by specific gluten protein composition and molecular weight distribution. In this study, the effect of the presence and absence of stripe rust on gluten protein fractions in Avocet near-isogenic lines with resistance genes Yr9, Yr10, and Yr15 was determined, compared to the stripe rust susceptible Avocet S. The results highlights a relationship between the presence of the stripe rust disease, disease resistance genes and protein quality, therefore, breeding programs should consider this relationship when aiming to enhance resistance breeding as this can affect the end-use quality of wheat. Although effects of the resistance genes were not consistent, significant variations in the different protein fractions were noted.